Global estimate of submarine groundwater discharge based on an observationally constrained radium isotope model. Issue 23 (3rd December 2014) - Kwon, Eun Young; Kim, Guebuem; Primeau, Francois; Moore, Willard S.; Cho, Hyung‐Mi; DeVries, Timothy; Sarmiento, Jorge L.; Charette, Matthew A.; Cho, Yang‐Ki
Abstract: Along the continental margins, rivers and submarine groundwater supply nutrients, trace elements, and radionuclides to the coastal ocean, supporting coastal ecosystems and, increasingly, causing harmful algal blooms and eutrophication. While the global magnitude of gauged riverine water discharge is well known, the magnitude of submarine groundwater discharge (SGD) is poorly constrained. Using an inverse model combined with a global compilation of 228 Ra observations, we show that the SGD integrated over the Atlantic and Indo‐Pacific Oceans between 60°S and 70°N is (12 ± 3) × 10 13  m 3  yr −1, which is 3 to 4 times greater than the freshwater fluxes into the oceans by rivers. Unlike the rivers, where more than half of the total flux is discharged into the Atlantic, about 70% of SGD flows into the Indo‐Pacific Oceans. We suggest that SGD is the dominant pathway for dissolved terrestrial materials to the global ocean, and this necessitates revisions for the budgets of chemical elements including carbon. Key Points: Global magnitude of SGD is measured using a radium‐228 budget Global SGD is 3 to 4 times greater than the river water fluxes into the oceans About 70% of SGD flows into the Indo‐Pacific Oceans